Early Sexual Behaviours and Academic Performance of In-school Adolescent Girls in Kathmandu Valley - Maharjan, Shyam Krishna; Devkota, Bhimsen; Budathoki, Chitra Bahadur (Journal of Health Promotion, 2018)
The purpose of the current study is to analyze the association between early sexual behaviour and academic achievement of adolescent girl students. Girl students as well as the health education teachers of higher secondary schools from three districts of Kathmandu valley and the stakeholders from respective areas were selected purposively covering the public as well as private schools. Data were collected through questionnaire, focus group discussions and key informant interview. Quantitative data were analyzed using SPSS while the qualitative data were transcribed and translated into English and thematically analyzed. It is revealed that almost all girls wanted to make friends from both sex, preferably from same sex. More than half of the girls had a boyfriend or boyfriends. Among the total who had boyfriends four out of ten had dated but only a small proportion (2%) had spent their time with their boyfriends. It was revealed that having a boyfriend is one of the main factors for initiating sexual activity due to pressure from their boyfriends. Around 28% were involved in different forms of sexual behaviour like kissing, hugging, body rubbing and touching sexual organs. However, very fewer (only 6 out of 400 girls) were involved in sexual activity and only half of those involved in sexual activity used condoms. Interviews also revealed that girls became shy when the matter of sex was taught in the classroom. They even could not talk freely about menstruation with teachers. The findings show that no statistical difference exists between sexual behaviour and academic performance of adolescent girl students of Kathmandu valley.Journal of Health Promotion Vol.6 2008, p.70-79